CONTESTED DOMESTIC SPACES: ANNE LANDSMAN'S "THE DEVIL'S CHIMNEY" - Nudelman, Jill (My University, 2006)
This dissertation interrogates Anne Landsman’s The Devil’s Chimney. The novel is narrated by the poor-white alcoholic, Connie, who imagines a story about Beatrice, an English colonist living on a farm in the Little Karoo. Connie, who is a product of the apartheid era, interweaves her own story with that of Beatrice’s and, in this way, comes to terms with her own memories, her abusive husband and the new South Africa. Connie deploys the genre of magical realism to create a defamiliarised farm setting for Beatrice’s narrative. She thus challenges the stereotypes associated with the traditional plaasroman and its patriarchal codes. These codes are also subverted in Connie’s representation of Beatrice, who contests her identity as the authoritative Englishwoman, as constructed by colonial discourse. In addition, Beatrice’s black domestic, Nomsa, is given voice and agency: facilities denied to her counterparts in colonial and apartheid fiction. Nomsa’s relationship with Beatrice is also characterised by subversion as it blurs the boundaries between colonised and coloniser. In this regard, the text demands a postcolonial reading. Connie, in narrating Beatrice’s and Nomsa’s stories, reinvents their invisible lives and, by doing so, is able to rewrite herself. In this, she tentatively envisions a future for herself and also potentially ‘narrates’ the nation, thus contributing to the new national literature. The nation is inscribed in the Cango caves, whose spaces witness the seminal episodes in Beatrice’s narrative. In these events, the caves ‘write’ the female body and women’s sexuality and the text thus calls for an engagement with feminism. The caves also inscribe South African history, the Western literary canon, the imagination and Landsman’s own voice. Hence, the caves assume the characteristics of a palimpsest. This, together with the metafictive elements of the novel, invites an encounter with postmodernism.
Student Number : 7805464 - MA dissertation - School of SLLS - Faculty of Arts
Keywords: Magical Realism (literature); home; feminism; postcolonialism; white women; South African literature; post-apartheid literature; literary history - South Africa; caves; space and time in literature